Investigation of acoustic, mechanical, and thermal properties of green composites reinforced with Kapok/Palm/Sisal natural fiber waste - Rajasekar Kannan; Syath Abuthakeer Syed Beer; Yohannes Admassu (Journal of Engineered Fibers and Fabrics)
This study presents the development and performance assessment of six composite samples (SC1–SC6) engineered for advanced applications requiring mechanical strength, thermal insulation, and acoustic efficiency. Each composite was analyzed for thickness, tensile strength, flexural strength, impact resistance, compressive strength, thermal conductivity, and sound absorption coefficient (SAC). SC1 demonstrated modest mechanical properties, with tensile strength of 12.79 MPa and SAC of 0.74%, while SC2 offered enhanced flexural (80.90 MPa) and compressive strength (14.47 MPa), along with the lowest thermal conductivity (0.048 W/mK) and the highest SAC (0.79%), highlighting its excellent insulation potential. SC3 exhibited superior tensile (36.53 MPa) and impact strength (16.46 J/m), though it’s SAC (0.65%) and thermal conductivity (0.053 W/mK) were moderate. SC4 recorded the highest flexural (96.42 MPa) and compressive strength (19.17 MPa), with strong impact resistance (18.82 J/m) and SAC of 0.76%, but a slightly higher thermal conductivity (0.058 W/mK). SC5 showed balanced attributes across all parameters, while SC6 demonstrated high overall mechanical strength, including flexural (90.67 MPa) and impact strength (18.78 J/m), though with the highest thermal conductivity (0.065 W/mK) and a notable SAC of 0.78%. The comparative analysis highlights trade-offs between thermal conductivity and acoustic performance. SC2 stands out for thermal and sound insulation, SC3 and SC4 are well-suited for load-bearing applications, and SC6 offers a versatile profile for multi-functional use. These results underscore the potential for customizing composite properties to meet diverse engineering needs.